EVALUASI MANAJEMEN BERBASIS SEKOLAH PADA PROGRAM PRAKTIK KERJA LAPANGAN DI SMK BALIKPAPAN - Firmansyah Firmansyah; Nurlaili Nurlaili; Widyatmike Gede Mulawarman; Noor Rachmawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the implementation of school-based management in Work-Based Learning (WBL) at Airlangga Health Vocational School Balikpapan. Employing a qualitative approach with the discrepancy evaluation model, it encompasses evaluations of design, installation, process, product, and cost analysis. Data were obtained from primary and secondary sources through interviews and documentation, subsequently analyzed through data collection, reduction, display, and conclusion drawing. The research findings indicate that the internship program planning has met the criteria, organizational aspects are in line with standards, and program execution has been successful. Monitoring and evaluation have also met the established standards. However, the assessment aspect requires improvement as it has not reached the desired standards. The main challenges in program implementation are financial issues and scheduling constraints. Based on the evaluation results, several program criteria need to be revised to enhance its quality.